O pensamento político na obra de Celso Furtado - Borges, Pedro Pereira (2007)
The objective of this Dissertation of Master's degree is to study the relationship between the intellectual path and Celso Furtado political practice and his influence in the Brazilian political extent. The study looked for to answer to two central problems of research: 1) could Furtado's literary work be included in the studies of Political Science and his/her consequent one to can inductive of producing effects transformers in the Brazilian political history? 2) which the conflicts and contradictions among the historian's theoretical extent, economist and academic and Celso Furtado practical politician? As for the approach in the analysis and interpretation of the data, this research is considered of the type qualitative, being treated of a theoretical and empiric nature study. It is ended that can include Celso Furtado literary work in the studies of Political Science and that she produced effects transformers in the Brazilian political history, mainly in the action planner of the State, in the improvement of the democratic institutions, in the defense of the State-nation and of the Brazilian internal market and in the need of a distribution of more equalitarian income. Several conflicts and contradictions were verified between the intellectual and Celso Furtado practical politician. But all of Celso Furtado contradictions can be qualified in instances purely intellectuals, because the author believed in the possibility of an intellectual action that took into account the "rupture epistemological between scientific knowledge and ideological knowledge". on the other hand, he became difficult, or else impossible, to frame Furtado's political positioning inside of the established requirements for Sartre, Bobbio, Gramsci and Said, without that resulted in a reductionism, being able to, besides, that attitude to be considered a respect lack to the studied author's intellectual and political path